2021
DOI: 10.1101/2021.03.29.437398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of candidate genes for self-compatibility in perennial ryegrass (Lolium perenneL.)

Abstract: Self-incompatibility (SI) is a genetic mechanism preventing self-pollination in approximately 40% of plant species. Two multiallelic loci, called S and Z, control the gametophytic SI system of the grass family (Poaceae), which contains all major forage grasses. Loci independent from S and Z have been reported to disrupt SI and lead to self-compatibility (SC). A locus causing SC in perennial ryegrass (Lolium perenne L.) was previously mapped on linkage group (LG) 5 in a F2 population segregating for SC. Using a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Genes underlying these loci likely have a function in the downstream cascade following the initial pollen–stigma recognition mediated by S and Z ( Do Canto et al , 2016 ). The most recent studies on non- S or non- Z sources of SC identified two genetically independent loci on LG 5 ( Arias-Aguirre et al , 2013 ; Do Canto et al , 2018 ; Cropano et al , 2021 ) and LG 6 ( Slatter et al , 2020 ) in two unrelated perennial ryegrass F 2 populations segregating for SC. In both populations, using in vitro self-pollinations ( Fig.…”
Section: Self-compatibility In the Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes underlying these loci likely have a function in the downstream cascade following the initial pollen–stigma recognition mediated by S and Z ( Do Canto et al , 2016 ). The most recent studies on non- S or non- Z sources of SC identified two genetically independent loci on LG 5 ( Arias-Aguirre et al , 2013 ; Do Canto et al , 2018 ; Cropano et al , 2021 ) and LG 6 ( Slatter et al , 2020 ) in two unrelated perennial ryegrass F 2 populations segregating for SC. In both populations, using in vitro self-pollinations ( Fig.…”
Section: Self-compatibility In the Grassesmentioning
confidence: 99%
“…In both cases, it was concluded that SC was under the control of a single gametophytically acting pollen gene. Furthermore, Cropano et al (2021) narrowed down the region to a 0.26-cM locus, allowing the identification of candidate genes that could be the target of functional characterization studies.…”
Section: Self-compatibility In the Grassesmentioning
confidence: 99%
“…The fact that both the S and Z candidates contain the same protein domain (DUF247) of unknown function warrants further investigation into the molecular role and evolutionary origin of this domain. Recently, this same team fine mapped a QTL for self‐compatibility (SC) on chromosome 5 of L. perenne (Cropano et al ., 2021). They reduced the region to a 3‐Mb segment containing 57 genes among which, seven were relevant candidates.…”
Section: Intraspecific Self‐incompatibility In Plantsmentioning
confidence: 99%